Enhancing Motivation to Study the Qur’an Through the Cooperative Learning Model Among Elementary School Students - Ferawati, Ferawati; Mislaini, Mislaini; Yufrizal, Yufrizal; Huda, Mudhiyatul; Mutathahirin, Mutathahirin (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2026)
Cooperative learning is an effective alternative for helping students develop enthusiasm and engagement in learning. In addition to creating a pleasant learning atmosphere, cooperative learning also makes students more active and confident in their study of the Qur’an. Through group collaboration, students can help one another in reading, memorizing, and understanding Quranic verses. Consequently, students’ motivation and engagement in learning are further enhanced. This study aims to analyze the effectiveness of the cooperative learning model in enhancing elementary school students’ motivation in learning Quranic material. The method used is aclassroom action research conducted in two cycles, focusing on improving the quality of learning and increasing student participation. The results of the study showed a significant increase in student learning motivation: the “very good” category increased by 19.35%, the “good” category increased by 16.11%, and the “poor” category decreased by 44.50%. These findings confirm that the cooperative learning model is an effective pedagogical approach for improving student motivation and learning outcomes in Quran instruction.